Individualized blood pressure targets during postcardiac arrest intensive care. Issue 3 (June 2020) - Skrifvars, Markus B.; Åneman, Anders; Ameloot, Koen
Abstract : Purpose of review: To discuss recent findings relevant to optimizing blood pressure targets in adult, postcardiac arrest (PCA) patients and whether to tailor these based on specific patient, cardiac arrest or treatment characteristics. Recent findings: Observational data suggest that mean arterial pressure (MAP) below 65–75 mmHg in PCA patients is associated with worse outcome. A higher MAP could be beneficial in patients with chronic hypertension who more frequently have a right shift of the cerebral autoregulation curve. Two recent randomized pilot trials compared lower and higher MAP targets during PCA care and found no significant effect on biomarkers of neurological injury. The haemodynamic interventions in those studies did not use any cerebral perfusion endpoints beyond a static MAP targets during ICU stay. Individualized, dynamic MAP targets based on assessments of cerebral perfusion and tailored to the specifics of the patient, cardiac arrest circumstances and treatment responses may be more conducive to improved outcomes. Pilot data suggest that near infrared spectroscopy monitoring may be used to determine the cerebral autoregulatory capacity and an optimal MAP, but this approach is yet to be tested in clinical trials. Summary: Current evidence suggests targeting a MAP of at least 65–75 mmHg in PCA patients. Future studies should focus on whether certain patient groups could benefit from higher and dynamic MAP targets.